E-066 Treatment of symptomatic venous sinus stenosis demonstrates associated venous waveform morphologic changes. (22nd July 2018) - West, J; Garner, R; Greeneway, G; Traunero, J; Aschenbrenner, C; Singh, J; Wolfe, S; Fargen, K
Abstract : Introduction/purpose: Idiopathic intracranial hypertension (IIH), otherwise known as pseudotumor cerebri or benign intracranial hypertension, is a syndrome defined by a severe headache in the setting of increased intracranial pressure (ICP) in the absence of an intracranial mass. The pathophysiology of IIH remains poorly understood. However, venous outflow obstruction detected by cerebral venous manometry at the transverse sinus has been recognized as a contributing factor in a subset of patients with IIH, and stent placement in this subset of patients is associated with good clinical outcomes. Surgeons often determine candidacy for stent placement based on the magnitude of the venous pressure gradient across the site of stenosis. Furthermore, there is little known about venous sinus pressure waveform morphology in patients with this condition or how it changes after stenting. The purpose of this study was to prospectively analyze patients' venous sinus waveforms, their component peaks, and the influence of stenosis or anesthesia on waveform morphology with a goal of ultimately providing insight into the waveform and pathological morphologic changes seen with venous sinus stenosis. Materials and methods: Fifteen patients with IIH were enrolled prospectively and underwent waveform recording during catheter venography and manometry. Ten patients (Group A) with venous sinus stenosis and pressure gradient >8 mmHg underwent waveform recording during awake venography and then pre- and post-stent manometry while under general anesthesia. Five control IIH patients (Group B) without a trans-stenosis gradient underwent awake recording only. Results: All Group A patients underwent successful stenting with reduction of their gradient from 15.1 (+6.19) mmHg to 1.2 (+0.60) mmHg. This resulted in statistically significant reduction of the transverse sinus amplitude from 8.3 mmHg to 2.8 mmHg (p<0.05). Qualitative evaluation of the venous sinus waveform morphology yielded a number of never before reported findings. In Group A patients before stenting, the observed venous waveform progressed from an ICP-dominated waveform to CVP-dominated waveform from the superior sagittal sinus to the internal jugular vein. Stenting abolished the pathologic high amplitude waveform and lowered the amplitude distal to the stenosis while smoothing the transition from the intracranial to central venous measurement points. Group B patients displayed respiratory variability of the waveform which was absent in 8/10 Group A patients. The use of general anesthesia appeared to blunt the waveform peaks in 5/10 Group A patients. Conclusion: In conclusion, the cerebral venous waveform morphology appears to be influenced by both the intracranial pressure (ICP) waveform and the central venous pressure (CVP) waveform. Additionally, venous sinus stenosis with significant venous outflow obstruction results in morphologic changes to the waveforms. After performing stenting in patients with stenosis, waveforms return to match the control group. Future studies should expand on the qualitative patterns described in this study and place a significant amount of consideration in determining the clinical and hemodynamic ramifications of these findings. Disclosures: J. West: None. R. Garner: None. G. Greeneway: None. J. Traunero: None. C. Aschenbrenner: None. J. Singh: None. S. Wolfe: None. K. Fargen: None.